An industrial IoT sensor system for high-temperature measurement. (October 2021) - Chang, Victor; Martin, Craig
Abstract: The world is changing, with more systems becoming automated through the Internet of Things (IoT). By the end of 2020, 38.5 billion connected devices are expected to be part of the IoT, which is an increase of 25.1 billion from 2015. With the digital revolution thoroughly underway, companies have been fully aware that statistical data can help their businesses thrive and increase efficiency. In this paper, the design and implementation of an Arduino sensor system used to record the temperature and location of ladle vessels for metallurgical purposes is presented. The Arduino microcontroller has multiple modules connected to it, including a K -Type thermocouple, Global-Positioning System (GPS) Shield, Real-time clock, and a Bluetooth module. Additionally, our system was fully tested to demonstrate that it could measure 1220 Celsius for twenty-two hours. Our work can contribute to the development of Industrial IoT and smart sensor services.